Wettability of three denture base materials to human saliva, saliva substitute, and distilled water: A comparative in vitro study - Pavithra K Ramanna (Wolters Kluwer Medknow Publications, 2018)
Aim: The purpose of this study was to compare the wettability of saliva, a saliva substitute, and distilled water to three denture base materials. Materials and Methods: Thirty specimens of each denture base material: Heat cure polymethylmethacrylate (DPI heat cure), high-impact polymethylmethacrylate (Trevalon HI), and nylon (Valplast) were fabricated. The specimens of each denture base material were divided into three groups of ten specimens. The advancing and receding contact angles of three media: a commercially available carboxymethylcellulose-based saliva substitute (WET MOUTH), human whole saliva, and distilled water, with each denture base material were determined using a goniometer. The contact angle hysteresis was calculated as the difference between the advancing and receding contact angles. The data were statistically analyzed using univariate analysis of variance and Duncan post hoc test. Results: Low-advancing and receding contact angles were demonstrated on high-impact heat-polymerized polymethylmethacrylate denture base material. Highest hysteresis values were calculated for nylon denture base material. Conclusion: Best wettability was demonstrated on high-impact heat-polymerized polymethylmethacrylate denture base material. Based on the high hysteresis values calculated with nylon denture base material, it would possibly provide better denture retention.